Voice and swallowing after total laryngectomy. (1st February 2018) - Arenaz Búa, Beatriz; Pendleton, Hillevi; Westin, Ulla; Rydell, Roland
Abstract: Background: Voice and swallowing problems are often seen in patients with advanced larynx cancer, after total laryngectomy (TL) and chemo/radiotherapy. The aim of this study was to determine the occurrence of voice and swallowing problems in patients who have been laryngectomised and investigate if these symptoms were related to age, time after TL, radiotherapy and TNM-classification. In addition, we studied how often the patients changed their voice prostheses and the need of therapeutic interventions after TL. Methods: Forty-five patients were included in the study and completed the Swedish version of the Sydney Swallow Questionnaire and the Voice Handicap Index-T. Results: Swallowing problems were reported by 89% of the patients and moderate-to-severe voice handicap was reported by 66%. Most of the subjects who had dysphagia also presented voice problems ( r s  = 0.67 p  ≤ .01). Additional therapeutic interventions to manage problems with voice and/or swallowing after TL were required in 62% of the patients. Conclusions: Swallowing and voice problems after TL are common. Thus, the preoperative information and assessment of these functions, as well as the treatment and the post-operative rehabilitation should be evaluated and optimised to provide better functional results after treatment of advanced larynx cancer.